دلالات أصوات أحكام التجويد وأثرها في فهم المبهم والمشكل من القرآن = The connotations of the sounds of the rules of Tajweed and its impact on understanding the enigmatic and equivocal from the Qur'an - Abdul Rasheed Al Balushi, Subaiya; Elatrash, Radwan Jamal Yousef; Abdo Khaled, Nashwan (IIUM Press, International Islamic University Malaysia, 2020)
تحدى الله  بكتابه العظيم أبلغ فصحاء العرب، فعجزوا أن يأتوا بسورة من مثله، وذُهِلت عقولهم بحروفه وكلمه، وعندما سمع بعضهم آيات القرآن الكريم أصابه الدهش الشديد، وأيقن أغلبهم في نهاية المطاف أنه ليس بكلام بشر. الأمر الذي دعا فئة العلماء المتخصصة في دراسات القرآن إلى التأمل في معانيه وبناء ألفاظه والوقوف على فواصله ومقاطعه وسكناته وحركاته ومداته وغناته تأملاً وتدبراً وتفقهاً وتبصراً وتذكراً، ومن أعظم علامات الإعجاز لهذا الكتاب العظيم هو عجز العلماء المستمر عن تفسير بعض ألفاظه وآياته تفسيراً متفقاً عليه، فوقفوا عند بعضها بسبب إيهام التعارض والتناقض في تفسير لفظة من ألفاظه والتي تحتمل أكثر من معنى، فخفي عليهم دلالة تلك اللفظة. نتيجة لذلك، ألّفوا علماً مستقلاً وسموه مشكل القرآن، وهو العلم الذي يقوم على تتبع الألفاظ المبهمة الخفية المعنى، وتوضيحها قدر الإمان، وبيان ما تحمل من أحكام ودلالات ومقاصد، ولهذا تم وضع الأسس والقواعد والضوابط والمناهج في التعامل مع مشكل القرآن الكريم، ومن هنا جاءت فكرة البحث حول مدى أثر قراءة القرآن الكريم بأحكام التجويد في حلّ ووضوح بعض إشكال الألفاظ القرآنية، ولهذا كان من الأليق لطبيعة هذا البحث استخدام المنهج الاستقرائي والمنهج التحليلي للوصول إلى أهم النتائج، ومن أهمها: أن لكل لفظة من ألفاظ القرآن دلالات خاصة تبعاً لأصوات التجويد التي تتحكم في مخارج حروفها، وكان ذلك من الأسس والمناهج التي استعان بها العلماء في حل مشكل بعض ألفاظ القرآن الكريم. ***************************************************************************************** God Almighty challengedthe well-acknowledgedArabs to come up with a book comparabletoAl-Quran, they were incapableto originatea manuscriptsimilar toit, and their minds were startledby itsletters and words, and when some of them heard the words of God, they were flabbergasted, and realized that it was not human words. Which called the group of scholars specializing in Qur’anicstudies to ruminateon its meanings, and how its words were fashioned. One of the grandest signs of miracle of this great book is the unceasing malfunction of intellectuals to decode some of its words and verses in an agreed manner, and they meditatedsome verses that appear to contradict one anotherand carries more than one meaning. Consequently, they could not divulgethe meanings and connotations of those terms. As a result, they authored an independent discipline and called it the equivocal science of the Qur’an. That is why the guidelines, procedures, and curricula were authored to deal precisely with this science. Hence,the idea of this research erects to discuss the effect of reading the Holy Qur’an with the rules of intonation to solve some enigmatic Quranic words. However, it was appropriate for the nature of this research to use the inductive and analytical method to reach the most important results. Among the most important results is the following: Every word of the Qur’an has special meanings according to the sounds of intonation that control the articulation of its letters, this was one of the methods used by Muslim scholars to solve the problem of some words of the Holy Qur’an.